Video streaming technologies using ActiveX and LabVIEW - Panoiu, M; Rat, C L; Panoiu, C (IOP conference series. Materials Science and Engineering, 2015)
The goal of this paper is to present the possibilities of remote image processing through data exchange between two programming technologies: LabVIEW and ActiveX. ActiveX refers to the process of controlling one program from another via ActiveX component; where one program acts as the client and the other as the server. LabVIEW can be either client or server. Both programs (client and server) exist independent of each other but are able to share information. The client communicates with the ActiveX objects that the server opens to allow the sharing of information [7]. In the case of video streaming [1] [2], most ActiveX controls can only display the data, being incapable of transforming it into a data type that LabVIEW can process. This becomes problematic when the system is used for remote image processing. The LabVIEW environment itself provides little if any possibilities for video streaming, and the methods it does offer are usually not high performance, but it possesses high performance toolkits and modules specialized in image processing, making it ideal for processing the captured data. Therefore, we chose to use existing software, specialized in video streaming along with LabVIEW and to capture the data provided by them, for further use, within LabVIEW. The software we studied (the ActiveX controls of a series of media players that utilize streaming technology) provide high quality data and a very small transmission delay, ensuring the reliability of the results of the image processing.